Effect of cadmium on adult mortality of Polydora sp. (Polychaeta: Spionidae) under laboratory conditions. - Herrera-Perez, Melissa; Méndez, Nuria (Revista de Biología Tropical, 2019)
Introduction: Several studies have demonstrated the effect of Cd on mortality and other physiological responses of some polychaete species. Objective: to evaluate the toxic effect of Cd on adults mortality of Polydora sp as a test species for ecotoxicological studies. Methods: The specimens were collected in the coastal wetland of Poza de la Arenilla, Callao, Peru. The organisms were acclimatized for two weeks with seawater and sediment and then, three days in seawater, with 30 ‰ of salinity and temperature between 20 to 22 °C. The organisms were exposed to the nominal concentrations 75, 11.25, 1.69, 0.25; 0.04 mg/L of Cd and a control. Three replicates of ten individuals per treatment were analyzed for 72 hours to register mortality. The Kruskal-Wallis and U-Man Whitney tests were applied to detect significant differences among treatments. Results: The adverse effect of Cd on mortality was much more evident in the treatments of 11.25 and 75 mg/L after the first 24 hours of exposure. The mean lethal concentration of Cd at 72h was 2.59 mg/L. Conclusions: the LC50 is in the same order of magnitude as other polychaete species. This is the first ecotoxicological study in Peru using polychaetes under laboratory conditions. It is suggested the use of Polydora sp as a test species in ecotoxicology experiments, using nominal sublethal concentrations of Cd not exceeding 1.6 mg/L. for the observation of several physiological responses.